2020
DOI: 10.1016/j.tmp.2020.100721
|View full text |Cite
|
Sign up to set email alerts
|

Tourism jobs in demand: Where the best contracts and high salaries go at online offers

Abstract: It has been suggested that the tourism sector is one in which temporary and low-skilled jobs abound. The aim of this study is to analyze the educational and experience requirements associated with job offers in tourism and their corresponding contracts and salaries. Nine thousand job advertisements were analyzed from one of the biggest employment websites in Spain. Online job offers allow a profile of employers' preferences to be drawn up in terms of occupations, educational levels and required experience, as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…We found that higher education (in tourism, if feasible) likely holds greater importance in obtaining a managerial position in large tourism companies and is often in tandem with experience [57], but it has a moderate impact when it comes to starting a business. The explanations come either from the relatively low entry barriers in the sector (as previously mentioned) or the pragmatism of decisionmakers, which may prioritize relevant experience in the field (in tourism, in managerial positions) over formal high education or corporate experiences, the so-called "ivory tower" mentality [12,54,56].…”
Section: "I Intended To Approach These 3 Points: Desire To Succeed Fi...mentioning
confidence: 87%
See 1 more Smart Citation
“…We found that higher education (in tourism, if feasible) likely holds greater importance in obtaining a managerial position in large tourism companies and is often in tandem with experience [57], but it has a moderate impact when it comes to starting a business. The explanations come either from the relatively low entry barriers in the sector (as previously mentioned) or the pragmatism of decisionmakers, which may prioritize relevant experience in the field (in tourism, in managerial positions) over formal high education or corporate experiences, the so-called "ivory tower" mentality [12,54,56].…”
Section: "I Intended To Approach These 3 Points: Desire To Succeed Fi...mentioning
confidence: 87%
“…Often, initial professional training in tourism is undervalued compared to work experience, practical training, and personality traits [56]. According to Marrero-Rodríguez et al [57], experience is considered to be a crucial asset in this sector, influencing employment (acting as a selection criterion), promotion, and various company performances (salary levels, turnover growth rate, profits, etc. ).…”
Section: Work Experience Network and Self-efficacymentioning
confidence: 99%
“…This has made it possible to develop new skills, strengthen social networks and have more autonomy (LaPan et al , 2016). The main phenomena for choosing the tourism and service sectors for employment are decent working conditions, salary structure and social status (Hussain and Endut, 2018; Marrero-Rodríguez et al , 2020). Gender equality helps to promote sustainable economic growth for a country (Arbache et al , 2010; Dorius and Firebaugh, 2010; Foley and Cooper, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…However, looking over the data and the jobs within the second professional group suggests that they should be divided into two. The resulting categories are as follows-CNO2 [47] codes, as classifiers of the job position, in brackets: first (11)(12)(13)(14)(15), second (21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38), third , and fourth (90-98).…”
Section: Methodsmentioning
confidence: 99%
“…Regarding this, the scope of this work is to analyse the hospitality and tourism industries-defined as the subgroups of the accommodation and catering of the CNAE-09 [22,23]. Such a decision relies on: (1) the importance of the tourism industry in Spain-12.7% Spanish employment and 12.6% of the GDP in 2019, according to the latest pre-COVID-19 pandemic data [24]; (2) the differences in the Spanish hospitality/tourism labour market with respect to other countries because of its weak internal mobility [25,26] but high turnover rates, which is higher than other industries [12,27]; (3) the distinguishing characteristics of the hospitality industry regarding jobs, wage differences, and labour stability [28]; (4) the feminisation of the industry, which may lead to differences in human capital returns and wage differences [12,29]; and (5) the particular labour market in Spain, which is characterised by high unemployment and turnover rates [30] and regular labour reforms [31,32], the last one coming into effect on 31st December 2021 [33]. All these elements suggest that the Spanish labour market and, more specifically, its hospitality industry, despite sharing some characteristics with other countries, deserves particular differentiation.…”
Section: Introductionmentioning
confidence: 99%